HUBUNGAN KECEMASAN MATEMATIKA DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IX PADA MATERI SPLDV - Aprilia Winardi, Monica Priska; Halini, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was found based on the students' low mathematical communication skills, which one can be caused by mathematics anxiety. These facts cause the researcher  be interested to find out more about the relationship between mathematics anxiety and students' mathematical communication skills. The research method used in this research was a quantitative descriptive, with the techniques of data collecting were measurement technique, direct communication technique, and indirect communication technique. The sample in this study were all the students of IX A class totaling 34 people, and selected by the simple random sampling technique. The research hypothesis was tested by the Product Moment correlation test, with the correlation value was  -0,604 and the significant value was  0,000. The results showed that there was a negative relationship between mathematics anxiety and students' mathematical communication skills in solving mathematical problems. So it can be concluded that the higher the level of mathematics anxiety students have, the lower their mathematical communication skills, and the lower the level of mathematics students' anxiety, the higher their mathematical communication skills. Keywords: Mathematical Anxiety, Mathematical Communication Ability, SPLDV